Are injured workers with higher rehabilitation service utilization less likely to be persistent opioid users? A cross-sectional study - Alyson K. Kwok; Nathan N. O'Hara; Andrew N. Pollak; Lyndsay M. O'Hara; Alexandra Herman; Christopher J. Welsh; Gerard P. Slobogean (BMC, 2019)
Abstract Background Given its role in treating musculoskeletal conditions, rehabilitation medicine may be an important factor in decreasing the use of opioids among injured workers. The primary objective was to determine if increased utilization of rehabilitation services was associated with decreased persistent opioid use among workers' compensation claimants. The secondary objective was to determine the combined association of rehabilitation service utilization and persistent opioid use with days of work lost due to injury. Methods Using Chesapeake Employers' Insurance Company claims data from 2008 to 2016, claimants with at least one filled opioid prescription within 90 days of injury were eligible for inclusion. The primary outcome was persistent opioid use, defined as at least one filled opioid prescription more than 90 days from injury. The secondary outcome was days lost due to injury. The primary variable of interest, rehabilitation service utilization, was quantified based on the number of rehabilitation service claims and grouped into five levels (no utilization, and four quartiles - low, medium, high, very high). Results Of the 9596 claimants included, 29% were persistent opioid users. Compared to claimants that did not utilize rehabilitation services, patients with very high rehabilitation utilization were nearly three times more likely (OR: 2.71, 95% CI: 2.28-3.23, p < 0.001) to be persistent opioid users and claimants with low and medium levels of rehabilitation utilization were less likely to be persistent opioid users (low OR: 0.20, 95%: 0.14-0.27, p < 0.001) (medium OR: 0.26, 95% CI: 0.21-0.32, p < 0.001). Compared to claimants that did not utilize rehabilitation services, very high rehabilitation utilization was associated with a 27% increase in days lost due to the injury (95% CI: 21.9-32.3, p < 0.001), while low (− 16.4, 95% CI: -21.3 - -11.5, p < 0.001) and medium (− 11.5, 95% CI: -21.6 - -13.8, p < 0.001) levels of rehabilitation utilization were associated with a decrease in days lost due to injury, adjusting for persistent opioid use. Conclusion Our analysis of insurance claims data revealed that low to moderate levels of rehabilitation was associated with reduced persistent opioid use and days lost to injury. Very high rehabilitation utilization was associated with increased persistent opioid use and increased time from work.